Mechanical and rheological properties of selected varieties of peppers. - Thomas, C. H.; Wan Ismail, Wan Ishak; Rollason, S. H. (American Society of Agricultural Engineer, 1980)
Stress-relaxation rates for eight varieties of peppers were measured. The specimens were loaded at 454,907 and 1361 grams and allowed to relax for time periods of 3.8 and 30 minutes. Stress levels used were 914, 1828 and 2741 gm/cm2. Floral Gem and Jalapeno varieties of peppers received the most attention.